PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE COOPERATIF INTEGRATED READING AND COMPOSITION (CIRC) UNTUK MENINGKATKAN KETERAMPILAN MENULIS PUISI SISWA KELAS V SD NEGERI 29 AIR PUTIH BENGKALIS - Syamsul, Muhammad; ', Syahrilfuddin; ', Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background problem in this research is the low skills of fifth grade student SD Negeri 29 Air Putih Bengkalis to write poetry. The purpose of this research is to improve the skills of fifth grade student to write poetry. This research is a classroom action research. Data collection instruments were used in this research were teachers and students observation sheet activities and writing poetry test skills. The results showed that this learning model can increase the activity of teachers and students and students' skills of writing poetry. At the first meeting of the first cycle, the activities of teachers rated at 45.83%. At the next meeting, be 66.67%. At the first meeting of the second cycle, the activities of teachers percentage to 83.33%, and at a second meeting be 93.83%. At the first meeting of the first cycle, the percentage of student activity amounted to 45.83%. At the next meeting, increased to 65.20%. In the second cycle, the first meeting, the percentage of the student activity becomes 79.17%. While the second meeting be 91.67%. In the first cycle, 2 students categorized very skilled writing poetry, 17 students categorized skilled, 10 students categorized quite skilled, and two students who fall into the category less skilled. In the second cycle, the number of students categorized as very skilled in writing poetry to 5 people, 22 students categorized skilled, and 4 students categorized quite skilled. The average of learning outcome at 70.97 for firts cycle and increased to 76.61 for second cycle. Keyword: Learning model Cooperatif Integrated Reading and Composition (CIRC), Skills of writing poetry.